Patient experience in a pediatric emergency department during COVID-19 - Beth Emerson; Erika Setzer (The Beryl Institute, 2020)
The COVID-19 pandemic has changed many dynamics in healthcare in the United States. This study explores an increase in patient experience (PE) scores in a pediatric emergency department. Visits were analyzed before and after March 8, 2020, corresponding with the first local case of COVID-19. Changes in the patient population and characteristics of survey responders were analyzed. Overall, the number of daily visits decreased (113 vs 36/day) and survey response rate decreased (3.7 vs 2.8%, p = 0.03), but PE scores increased (87.21 to 93.73, p = 0.002). Comparatively, an increase in patients with higher acuity levels by Emergency Severity Index (ESI), white/Caucasian race, and non-Hispanic ethnicity were observed in the population. Similarly, responders were comprised of higher ESI and a similar racial shift. No correlations, however, were identified between these factors and PE score. Overall, while the data suggest some changes in demographics and acuity, they do not adequately account for the increase in PE score. Further evaluation of the patient/provider relationship during a global pandemic is justified. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.